2014
DOI: 10.1002/app.41419
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, electrical, and mechanical properties of tween 80/span 80–based organogels and its application in iontophoretic drug delivery

Abstract: The present study describes the preparation and characterization of the Tween 80/Span 80 and sunflower oil-based organogels. Organogels were characterized using microscopy, X-ray diffraction, thermal, mechanical, and electrical techniques. The properties were found to be dependent on the proportion of the water : surfactant mixture. The in vitro drug release studies were performed under electrical potential. The drug release in the presence of electrical current was compared with the passive drug release. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The bigels were prepared by fluid‐filled structure mechanism as per our previously reported method with slight modifications . The surfactant mixture of span 80: tween 80 (1 : 2, w/w) was used as the liquid gelator ( S mix ).…”
Section: Methodsmentioning
confidence: 99%
“…The bigels were prepared by fluid‐filled structure mechanism as per our previously reported method with slight modifications . The surfactant mixture of span 80: tween 80 (1 : 2, w/w) was used as the liquid gelator ( S mix ).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, a 1.4-fold enhancement in CPDR was recorded for d-AuG0 in the active mode compared to that in the passive mode. Such an increment, although minor, was not an unexpected outcome since nonconducting oleogels have been reported to be slightly responsive toward iontophoretic drug release . However, a striking 3.2-fold increase was observed in the case of d-AuG4 in the active mode compared to that in the passive mode.…”
Section: Discussionmentioning
confidence: 83%
“…Such an increment, although minor, was not an unexpected outcome since nonconducting oleogels have been reported to be slightly responsive toward iontophoretic drug release. 48 However, a striking 3.2-fold increase was observed in the case of d-AuG4 in the active mode compared to that in the passive mode. Clearly, the iontophoretic effect due to the presence of AuNPs was the major responsible factor prevalent in this case.…”
Section: Discussionmentioning
confidence: 93%
“…Hence, it can be concluded that the addition of GO helped in the formation of a more stable structure in the formulations that had higher levels of GO. Sagiri et al (2015) have mentioned that %SR is the measure of the molecular arrangement of all the constituents that are present in the gel [ 73 ]. Hence, the %SR was calculated to study the percentage decrease in the force values from the maximum to the end of the relaxation time (Equation (5)).…”
Section: Resultsmentioning
confidence: 99%